2012
DOI: 10.1165/rcmb.2012-0068oc
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepithelial Bodies as Mechanotransducers in the Intrapulmonary Airway Epithelium

Abstract: In rodent lungs, a major part of the myelinated vagal airway afferents selectively contacts pulmonary neuroepithelial bodies (NEBs). Because most myelinated vagal airway afferents concern physiologically characterized mechanoreceptors, the present study aimed at unraveling the potential involvement of NEB cells in transducing mechanosensory information from the airways to the central nervous system. Physiological studies were performed using confocal Ca(2+) imaging of airway epithelium in murine lung slices. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Accordingly, it is probable that at least a proportion of these cells are innervated by vagal afferents (42). Although the formation of cytoneural junctions is generally regarded as unlikely, the close association of fibers with epithelial cells is strongly suggestive of the presence of afferent signaling (43). The chemical mediator for signaling between PNECs and vagal afferents is not known but may be ATP (43)(44)(45), which would be consistent with recent clinical studies of cough (46).…”
Section: Observationssupporting
confidence: 66%
“…Accordingly, it is probable that at least a proportion of these cells are innervated by vagal afferents (42). Although the formation of cytoneural junctions is generally regarded as unlikely, the close association of fibers with epithelial cells is strongly suggestive of the presence of afferent signaling (43). The chemical mediator for signaling between PNECs and vagal afferents is not known but may be ATP (43)(44)(45), which would be consistent with recent clinical studies of cough (46).…”
Section: Observationssupporting
confidence: 66%
“…In this way, we were able to demonstrate that ATP released from activated NEB cells typically gives rise to a delayed activation of Clara-like cells (De Proost et al, 2009;Lembrechts et al, 2012). In the present study, activation of CaSR expressed on NEB cells resulted in a delayed [Ca 2+ ] i rise in Clara-like cells, indicating that CaSR activation in NEB cells leads to [Ca 2+ ] i mediated exocytosis.…”
Section: Discussionsupporting
confidence: 65%
“…When local stimuli activate the release of secretory products from NEB cells, sensory nerve fibers in synaptic contact are believed to depolarize, triggering action potentials that can reach the CNS. The best characterized mechanism so far is the [Ca 2+ ] i -mediated release of ATP from activated NEB cells (De Proost et al, 2009;Lembrechts et al, 2012) influencing the P2X 2/3 ATP receptors expressed on the terminals of a population of vagal afferents that contacts pulmonary NEBs in rodents (Brouns et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNECs of the bronchiolar epithelium are also thought to serve as niche cells for naphthalene-resistant variant club cells (Guha et al, 2012;Hong et al, 2001). Several studies have suggested that PNECs perform many other functions including oxygen sensing, mechanotransduction, immune cell recruitment, and chemosensing (Branchfield et al, 2016;Lembrechts et al, 2012;Pan et al, 2002). Some of these functions are presumably mediated in part through their connections with nerve fibers.…”
Section: Neuroendocrine Cellsmentioning
confidence: 99%